2013
DOI: 10.1016/j.numecd.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Absence of an independent association between serum uric acid and left ventricular mass in Caucasian hypertensive women and men

Abstract: Background and aim: Experimentally uric acid may induce cardiomyocyte growth and interstitial fibrosis of the heart. However, clinical studies exploring the relationship between serum uric acid (SUA) and left ventricular (LV) mass yielded conflicting results.The aim of our study was to evaluate the relationships between SUA and LV mass in a large group of Caucasian essential hypertensive subjects. Methods and results: We enrolled 534 hypertensive patients free of cardiovascular complications and without severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
9
1
2
Order By: Relevance
“…The same association was observed in a study of 619 hypertensive patients who were followed for 34 months, showing that the combination of hyperuricaemia with LV hypertrophy was an independent predictor of cardiovascular events . Subsequent observations confirmed the association between uric acid and LV mass, although this was found to be gender related and a recent study conducted on 534 uncomplicated hypertensive patients has reported an association between circulating uric acid and LV mass index only in women . At opposite, no independent association of uric acid levels with LV mass was reported in a study of 580 newly diagnosed, never treated, hypertensive patients with relatively low prevalence of hyperuricaemia and in other large studies .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The same association was observed in a study of 619 hypertensive patients who were followed for 34 months, showing that the combination of hyperuricaemia with LV hypertrophy was an independent predictor of cardiovascular events . Subsequent observations confirmed the association between uric acid and LV mass, although this was found to be gender related and a recent study conducted on 534 uncomplicated hypertensive patients has reported an association between circulating uric acid and LV mass index only in women . At opposite, no independent association of uric acid levels with LV mass was reported in a study of 580 newly diagnosed, never treated, hypertensive patients with relatively low prevalence of hyperuricaemia and in other large studies .…”
Section: Discussionmentioning
confidence: 53%
“…Hyperuricaemia is frequently detected in patients with the metabolic syndrome and prospective studies have reported that elevated uric acid levels are associated with an increased risk of myocardial infarction and stroke and with worse LV function in heart failure patients . Studies conducted in the last decade have evaluated the relationships between uric acid levels and LV mass in hypertension reporting inconsistent findings , mostly because of interference of components of the metabolic syndrome. Moreover, different findings between men and women were reported in some studies .…”
Section: Introductionmentioning
confidence: 99%
“…It may be interesting to note that hyperuricemia is reportedly associated with increased cardiovascular events only in males but not in females. 26) Several studies, mainly among Caucasians, reported that serum high UA was not associated with LVH, [27][28][29] however, care should be taken in interpreting these results because most of these studies were done in somewhat obese subjects with electrocardiograms.…”
Section: Discussionmentioning
confidence: 99%
“…В ряде работ показана связь ГУ с ММЛЖ и другими маркерами органного поражения [2,16] напротив, не выявили значимой ассоциации МК с ММЛЖ, поражением сонных артерий и кардиова-скулярной заболеваемостью [17,18]. Ранее нами и рядом других авторов было показано участие МК в развитии окислительного стресса, иници-ации эндотелиальной дисфункции, изменении цитоки-нового статуса, нарушении гемостаза и микроциркуля-ции [16,19].…”
Section: Discussionunclassified